Long‐Term Impacts of Global Solid Biofuel Emissions on Ambient Air Quality and Human Health for 2000–2019 - Debatosh B. Partha; Ying Xiong; Noah Prime; Steven J. Smith; Yaoxian Huang (GeoHealth)
Abstract Globally, solid biofuels (SB) have been widely used for household cooking and energy production for decades due to electricity shortages and socio‐economic barriers to adopting renewable energy alternatives. This has detrimental effects on air quality, human health, and climate through trace gas and aerosol emissions. Despite numerous studies, the long‐term consequences of SB emissions remain poorly understood. Here, we use the Community Earth System Model and the Community Emissions Data System emission inventory to investigate the SB emission impacts on air quality and human health for 2000–2019. Global SB emission increased the ambient PM2.5 (particulate matter with aerodynamic diameters ≤2.5 μm) and ozone (O3) concentrations up to 23.61 μg/m3 and 13.69 ppbv, with significant effects found in India, China, and the Rest of Asia (ROA). Our study estimates total annual premature deaths (APDs) associated with global SB‐attributable PM2.5 and O3 exposure as 1.11 million [95% confidence interval (95% CI): 1.00–1.22 million] in 2000 up to 1.43 million (95% CI: 1.30–1.56 million) in 2019. China's SB emissions and associated APDs have reduced substantially, whereas India and ROA had a major leap in both estimates in 2019 compared to 2000. China's progress in cutting residential SB emissions accounts for its improvements. Our study urges the reduction of SB usage and emissions to potentially improve overall air quality and human health conditions, especially in highly populated, low‐ and middle‐income countries, where the poor air quality and associated health burden attributable to SB emissions are estimated to be higher.